2013
DOI: 10.1620/tjem.230.33
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Learning Motivation Toward Technical Knowledge and Their Ethics Regarding Patients’ Rights

Abstract: Nursing students must develop their abilities to provide appropriate nursing services. They need to acquire the level of nursing knowledge to pass the national examination according to Japanese law. Moreover, even if the awareness of the rights of people who receive nursing services increases, students must not have a sense of resistance toward those rights. Therefore, we investigated the factors associated with students' motivation to pass their examination and such a sense of resistance. We produced items re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
(18 reference statements)
0
8
1
1
Order By: Relevance
“…In our former study (Kudo et al 2013), we reported nursing students' sense of ethics and learning motivation. Because the subjects of the present study were the same as in the former study, we only described the outline of the subjects in this study.…”
Section: Subjects and Methods Of The Questionnaire Distribution And Cmentioning
confidence: 97%
See 3 more Smart Citations
“…In our former study (Kudo et al 2013), we reported nursing students' sense of ethics and learning motivation. Because the subjects of the present study were the same as in the former study, we only described the outline of the subjects in this study.…”
Section: Subjects and Methods Of The Questionnaire Distribution And Cmentioning
confidence: 97%
“…Because the subjects of the present study were the same as in the former study, we only described the outline of the subjects in this study. For more detail, please see our former study (Kudo et al 2013).…”
Section: Subjects and Methods Of The Questionnaire Distribution And Cmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the educational design and working environment do affect student's ability to perform in the clinical training settings [9]. Such factors are assumed also to negatively influence intrinsic motivation for learning and knowledge acquisition among nursing students [10]. While real and hands on teaching for nursing students seems beneficial and have significant impact on their clinical competency, workplace environment and risks concerning clinical demonstration on patients would urge finding less risky solution with equal benefits.…”
mentioning
confidence: 99%